Assessing the Effect of School‐Based Health Centers on Achievement of National Performance Measures. (12th July 2021) - Hussaini, Khaleel S.; Offutt‐Powell, Tabatha; James, Gloria; Koumans, Emilia H.
ABSTRACT: BACKGROUND: We assess the impact of School‐Based Health Centers (SBHCs) on National Performance Measures (NPMs) related to health care access and utilization among Medicaid‐insured youth in Delaware. METHODS: Our retrospective analysis of Delaware's SBHC program data linked with Medicaid claims during 2014‐2016 for 13 to 18‐year‐olds assessed achievement of NPMs and use of mental health services using propensity scores. We estimated crude and adjusted prevalence ratios (APR) for SBHC‐enrolled compared with non‐enrolled youth. RESULTS: Students enrolled in SBHCs had more health care visits (M = 8.7; 95% CI: 7.9‐9.5) compared with non‐SBHC‐enrolled youth (M = 4.5; 95% CI: 4.3‐4.7). Compared with non‐SBHC, those enrolled in SBHCs were more likely to receive: well‐child visits (APR = 1.2; 95% CI: 1.1‐1.3); annual risk assessment (APR = 11.0; 95% CI: 6.9‐17.5); BMI screening (APR = 5.6; 95% CI: 3.3‐9.4); nutrition counseling (APR = 4.1; 95% CI: 2.8‐6.0); physical activity counseling (APR = 6.3; 95% CI: 4.2‐9.4); STIs and chlamydia screening (APR = 1.9; 95% CI: 1.3‐2.8); mental health visits (APR = 2.6; 95% CI: 2.2‐3.1). CONCLUSIONS: We found that among Medicaid‐insured youth, those enrolled in SBHCs vs not enrolled in SBHCs had greater health care utilization as evident from NPMs and mental health services.